Laparoscopic cholecystectomy in patients with situs inversus totalis: surgical challenges and technical adaptations - Sandoval Polito, Alfonso; Ruiz Ruiz, Diego; Barragán Ortega, Jeffrey; Tamayo-Gómez, Manuel Esaú; Mendoza Lopez, Hever Jair; Gómez Roblero, Patricia; de Luna Vega, Dalia Azucena; Salzillo Cardona, Jonathan Mario; Ortega Arenas, Cristóbal Jerónimo; Cruz Perez, Kevin Darian; Manrriquez-Avena, Ivan; Mondragon Espinoza, Ricardo; et al. (International Surgery Journal, 2026)
Gallstone disease is one of the most common gastrointestinal disorders worldwide, and laparoscopic cholecystectomy has become the gold standard treatment for symptomatic cholelithiasis and acute cholecystitis. Situs inversus totalis (SIT) is a rare congenital condition characterized by mirror-image transposition of thoracic and abdominal organs, which may complicate both the clinical diagnosis and surgical management of biliary disease due to altered anatomical orientation. A targeted systematic review of the literature was conducted using the PubMed/Medline database to identify studies reporting laparoscopic cholecystectomy in patients with SIT. The search included publications from January 2010 to March 2026 using a combination of Medical Subject Headings (MeSH) and free-text terms related to situs inversus and laparoscopic cholecystectomy. Titles and abstracts were screened for relevance, followed by full-text review of eligible studies. Case reports and case series describing operative techniques, clinical presentation, and surgical outcomes were included. Data were extracted and synthesized narratively due to the heterogeneity of the available evidence. The literature search identified seven relevant studies, consisting primarily of case reports and small case series from multiple geographic regions. Most patients presented with symptomatic cholelithiasis or acute cholecystitis, often characterized by atypical left-sided abdominal pain due to mirror-image anatomy. Across the included studies, laparoscopic cholecystectomy was successfully performed with technical modifications such as mirrored trocar placement, adjusted surgeon positioning, and ergonomic adaptations during dissection. Postoperative outcomes were generally favorable, with most patients experiencing uneventful recovery and no significant intraoperative or postoperative complications. Laparoscopic cholecystectomy can be safely and effectively performed in patients with SIT when appropriate preoperative recognition and intraoperative technical adaptations are applied. Awareness of the reversed anatomical orientation, careful operative planning, and strict adherence to established principles of safe laparoscopic surgery are essential to minimize operative risk. Further multicenter studies are needed to better define standardized surgical strategies and outcomes in this rare clinical scenario.